Sosialisasi Penggunaan Aplikasi Tinkercad Kepada Peserta Didik MAN 1 Mandailing Natal - Fadilah, Rizki; aisyah; Siregar, Evitamala (Yayasan Kajian Riset Dan Pengembangan Radisi, 2025)
Education is a process of learning and developing individual potential through teaching, training and guidance. The aim of education is to develop individual abilities, knowledge and character to become productive and responsible individuals. One of the services that can be done to achieve educational goals is training or socialization that supports learning with the help of technology. Technology provides convenience and efficient speed in the learning process. Training is carried out with the help of an application called Tinkercad. The use of applications in this training was carried out because the learning process using the laboratory was not optimal. The use of laboratories is less than optimal, causing practicums to be rarely carried out. So E-LKPD training was carried out with the help of the Tinkercad application. The location of the socialization was held at MAN 1 Mandailing Natal in Panyabungan, specifically for class XII students. The results of evaluations and testimonials showed that students felt more enthusiastic about doing practicum so that learning was more active. The simple use of the Tinkercad application makes it easy for students to use it.